Initial commented checklist of Iranian mayflies, with new area records and description of Procloeon caspicum sp. n. (Insecta, Ephemeroptera, Baetidae) - Bojková, Jindřiška; Sroka, Pavel; Soldán, Tomáš; Namin, Javid Imanpour; Staniczek, Arnold H; Polášek, Marek; Hrivniak, Ľuboš; Abdoli, Ashgar; Godunko, Roman J (ZooKeys, 2018)
An initial checklist of mayflies (Ephemeroptera) of Iran is compiled based on critical review of available literature data, complemented with new data from 38 localities of Gilan and Ardabil provinces. At present, altogether only 46 species and 25 genera are known from Iran, 18 species are reported as new to Iran in this study. Some previously published data are critically evaluated and doubtful taxa are excluded from the list. Basic analysis of the distribution and biogeography of recorded species is given. Procloeon (Pseudocentroptilum) caspicum Sroka, sp. n. is described based on mature larva and egg. Critical differential diagnostic characters distinguishing the species from related taxa are discussed in detail.
Keywords: faunistic research; taxonomy; Middle East; biogeography; aquatic biodiversity